Organochlorine exposure and breast cancer risk in Colombian women Exposição a organoclorados e risco de câncer de mama em mulheres colombianas - P. Olaya-Contreras; J. Rodríguez-Villamil; H. J. Posso-Valencia; J. E. Cortez (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
An epidemiological study was performed in Santafé de Bogotá, Colombia, with a total of 306 women enrolled, including 153 incident BC cases and 153 age-matched controls. The objective of this study was to evaluate the association between BC risk and serum dichlorodiphenyl-dichloroethene (DDE) levels. Sociodemographic and reproductive data, diet, and past exposure to pesticides were obtained through a structured questionnaire. Chemical analysis of samples was performed by high resolution gas chromatography-ECD. Likelihood of developing BC by exposure to these substances was evaluated through odds ratios (OR) adjusted for: first-child breast-feeding, family BC history, body mass index (BMI), parity, and menopausal status. Data analysis was performed by conditional logistic regression techniques. Adjusted OR for exposure to serum DDE and BC suggests an increase risk of BC in the higher category of DDE exposure (OR = 1.95; CI 1.10-3.52). The test for trend was not statistically significant (p = 0.09). We confirm that serum DDE levels bear a positive association to risk of BC and could support the association between risk of BC and burden of DDE exposure. Em estudo epidemiológico realizado em Santa Fé de Bogotá, Colômbia, 153 casos incidentes de câncer de mama (CM) foram comparados com 153 controles, pareados por idade. O objetivo deste estudo foi avaliar a associação entre o risco de CM e níveis séricos do pesticida DDT (DDE). Dados reprodutivos e sócio-demográficos, características da dieta e informação sobre exposição pregressa a pesticidas foram obtidos por meio de questionário. A análise química de amostras de sangue foi realizada através de cromatografia a gaz de alta resolução - ECD. A verossimelhança de desenvolver CM como decorrência de exposição a estas substâncias foi avaliada através de odds ratios (OR), obtidas por técnicas de regressão logística condicional, ajustadas para amamentação do primogênito, história familiar de CM, índice de massa corporal, paridade e presença de menopausa. As OR ajustadas sugerem um risco aumentado de CM no estrato de maior exposição a DDE (OR = 1,95; C.I. 1,10-3,52), embora o teste de tendência fosse estatisticamente não significativo (p = 0,09). Os resultados encontrados constataram que os níveis séricos de DDE estão positivamente associados com o risco de CM, e poderiam apoiar a hipótese desta associação.